A Painful Beginning: Early Life Surgery Produces Long-Term Behavioral Disruption in the Rat - Ririe, Douglas G.; Eisenach, James C.; Martin, Thomas J. (Frontiers in Behavioral Neuroscience, 2021)
Early life surgery produces peripheral nociceptive activation, inflammation, and stress. Early life nociceptive input and inflammation have been shown to produce long term processing changes that are not restricted to the dermatome of injury. Additionally stress has shown long term effects on anxiety, depression, learning and maladaptive behaviors including substance abuse disorder and we hypothesized that early life surgery would have long term effects on theses complex behaviors in later life. In this study surgery in the rat hindpaw was performed to determine if there are long-term effects on anxiety, depression, audiovisual attention, and opioid reward behaviors. Male animals received paw incision surgery and anesthesia or anesthesia alone (sham) at postnatal day 6. At 10 weeks after surgery, open field center zone entries were decreased, a measure of anxiety (n=20) (P=0.03) (effect size, Cohen's d =0.80). No difference was found in the tail suspension test as a measure of depression. At 16-20 weeks, attentional performance in an operant task was similar between groups at baseline and decreased with audiovisual distraction in both groups (P<0.001) (effect size, η2=0.25), but distraction revealed a persistent impairment in performance in the surgery group (n=8) (P=0.04) (effect size, η2=0.13). Opioid reward was measured using heroin self-administration at 16-24 weeks. Heroin intake increased over time in both groups during 24-h free access (P<0.001), but was greater in the surgery group (P=0.045), with a significant interaction between time and treatment (P<0.001) (effect size, Cohen f 2= 0.36). These results demonstrate long-term disruptions in complex behaviors from surgical incision under anesthesia. Future studies to explore sex differences in early life surgery and the attendant peripheral neuronal input, stress, and inflammation will be valuable to understand emerging learning deficits, anxiety, attentional dysfunction, and opioid reward and their mechanisms. This will be valuable to develop optimal approaches to mitigate the long term effects of surgery in early life.